A community based intervention to modify preventive behaviors of cutaneous leishmaniasis in children: a randomized controlled trial based on PRECEDE PROCEED model - Hossein Jajarmi; Seyedeh Belin Tavakoli sani; Asma pourtaheri; Mahdi Gholian-Aval; Habibollah Esmaily; Seyed Hamid Hosseini; Rezvan Rajabzadeh; Hadi Tehrani (BMC, 2024)
Abstract Objectives Iran ranks among the top six countries globally with a significant incidence of Cutaneous Leishmaniasis (CL). Using planning models is one community-based intervention to promote preventive behaviors. The purpose of our study was to evaluate the effectiveness of the PRECEDE-PROCEED model (PPM) in modifying preventive behaviors related to CL in children through mother training in a community intervention. Methods A randomized controlled trial based on the PPM model was conducted on 168 mothers (intervention (n = 84) and control group (n = 84) with 10 years old children in the rural areas of Iran. Mothers from 7 village areas were randomly allocated to the intervention (2 village) and control groups (5 village). The intervention group received a program comprising eight 90-minute training sessions and environmental interventions. In this study, we utilized the PPM as a framework to design the questionnaires on Leishmaniosis prevention behavior. Participants in both groups completed the questionnaires at baseline (before the intervention), immediately after the intervention, and at the 2-month follow-up. Analysis of the data was conducted utilizing SPSS20, with statistical significance set at p < 0.05. Results Compared to the control group, the intervention group showed significant increases in knowledge, enabling factors, reinforcing factors, attitude, and preventive behaviors related to Cutaneous Leishmaniasis over time from baseline to follow-up (P < 0.001). No significant differences (P > 0.05) were observed in the alterations of the PPM construct, knowledge, and preventive behaviors within the control group from pre-intervention to follow-up. Conclusions Community (education and environmental) intervention based on PPM is feasible and acceptable to modify preventive behaviors of Cutaneous Leishmaniasis in children by increasing a mother's knowledge and attitude as well as changing enabling and reinforcing factors. Trial registration IRCT20160619028529N8.